Changes in sternal perfusion following internal mammary artery bypass surgery - Taeger, Christian; Klein, Konstantin; Horch, Raymund E.; Weyand, Michael; Beier, Justus (Clinical Hemorheology and Microcirculation, 2017)
BACKGROUND: Coronary bypass surgery using the internal mammary artery (IMA) is among the most commonly performed procedures in treatment of advanced coronary vessel disease. Further, bilateral harvesting of the IMA is associated with increased rates of sternal wound infections. OBJECTIVE: This study aimed to explore changes in sternal perfusion, following left internal mammary artery (LIMA) harvesting. METHODS: 60 patients were divided equally into intervention- and control cohorts and underwent assessment of oxygen saturation (sO2) and relative blood flow (RBF) by laser doppler flowmetry remission spectroscopy preoperatively, 24 h and 72 h postoperatively. RESULTS: 24 h postoperatively a significant decrease of sO2 and RBF could be detected in LIMA harvest patients. After 72 h this difference disappeared. The side comparison within the groups 24 h postoperatively revealed a reduction of sO2 on the LIMA side within both groups. Regarding the 24 h RBF in side comparison, no significant differences could be detected within the groups. The 72 h side comparison showed an increased RBF for the non-LIMA side within the control group. CONCLUSIONS: The use of the LIMA may lead to significant decreases in local tissue oxygen saturation and RBF. This reduction is mostly distinct within the first 3 days postoperatively and may influence sternal wound infections.
EVALuna2:32852